Secondary battery, battery pack, and energy storage system
By using a solid electrolyte with a double-layer structure in the secondary battery, and using the self-polarized polarization electric field of barium titanate particles, the problem of dendrites in the secondary battery is solved, and the charging and discharging performance and safety are improved.
Patent Information
- Application Number
- CN202310963804.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
AI Technical Summary
During the cycle of the secondary battery, dendrites are easily generated on the surface of the metal negative electrode, resulting in the safety hazards of flammable and explosiveness of the secondary battery and affecting the circulation performance of the secondary battery.
A solid electrolyte with a bilayer structure is used, including a polymer matrix layer and an interface composite layer, which contains barium titanate particles. The polarization electric field generated by the self-polarization of barium titanate particles balances the electric field at the interface, so that metal ions are uniformly deposited on the surface of the negative electrode sheet, and dendrites are inhibited.
It effectively inhibits dendrites on the surface of the negative electrode sheet, improves the charging and discharging performance and safety of the secondary battery, and improves the mechanical strength of the solid electrolyte, reducing the possibility of dendrites puncture.
Smart Images

Figure CN119447441A_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present application relate to the field of energy technology, and more specifically, to a secondary battery, a battery pack, and an energy storage system. Background Art
[0002] With the continuous development and widespread application of clean energy, higher requirements are placed on the charge and discharge performance and safety of secondary batteries. Metal anodes such as lithium and sodium are considered to be high-energy anode materials with broad development prospects due to their high theoretical specific capacity and low electrochemical potential.
[0003] However, currently, during the cycle process of secondary batteries, dendrites (such as lithium dendrites or sodium dendrites) are easily generated on the surface of the metal negative electrode. Dendrites can easily cause safety hazards such as flammability and explosion of secondary batteries, and can easily lead to a decrease in the cycle performance of secondary batteries, thereby failing to meet the needs of improving the comprehensive performance of secondary batteries. Summary of the invention
[0004] The embodiments of the present application provide a secondary battery, a battery pack, an energy storage system and an electric vehicle, the purpose of which is to inhibit the growth of dendrites on the surface of the negative electrode plate in the secondary battery, which is beneficial to improving the charging and discharging performance and safety of the secondary battery.
[0005] In a first aspect, a secondary battery is provided, which includes: a negative electrode plate, a positive electrode plate and a solid electrolyte, wherein the solid electrolyte is located between the positive electrode plate and the negative electrode plate; wherein the solid electrolyte includes: a polymer matrix layer, wherein the polymer matrix layer includes a first polymer; an interface composite layer, wherein the interface composite layer includes a second polymer and barium titanate particles; the polymer matrix layer and the interface composite layer are stacked in sequence, wherein the interface composite layer is located between the polymer matrix layer and the negative electrode plate.
[0006] It should be understood that the first polymer and the second polymer can be polymers that can conduct ions but not conduct electricity, so as to serve as a transport carrier for metal ions between the positive electrode plate and the negative electrode plate.
[0007] It should also be understood that under the action of the electric field at the interface between the negative electrode plate and the composite interface layer, the barium titanate particles in the composite interface layer can be self-polarized, generating a self-polarization electric field in the opposite direction to the electric field at the interface. The self-polarization electric field can be used to balance the electric field at the interface, so that the electric field at the interface is evenly distributed.
[0008] In the above technical solution, the solid electrolyte is set as a double-layer structure, and the composite interface layer containing barium titanate in the double-layer structure is used as the interface layer where the solid electrolyte contacts the negative electrode plate. During the charging process of the secondary battery, the polarization electric field generated by the barium titanate is used to make the electric field at the interface where the negative electrode plate contacts the composite interface layer uniformly distributed, thereby guiding the metal ions in the composite interface layer to be uniformly deposited on the surface of the negative electrode plate. In this way, it is beneficial to inhibit the growth of dendrites on the surface of the negative electrode plate, and can improve the charge and discharge performance and safety of the secondary battery. In addition, the solid electrolyte with a double-layer structure has strong mechanical strength, which can reduce the possibility of dendrites on the surface of the negative electrode plate piercing the solid electrolyte, which is beneficial to further improve the safety of the secondary battery.
[0009] In combination with the first aspect, in certain implementations of the first aspect, in the interface composite layer, a mass ratio of the barium titanate particles to the second polymer ranges from 0.1 to 0.25.
[0010] In the above technical scheme, by setting the mass ratio of the barium titanate particles and the second polymer in the composite interface layer within an appropriate range, it is possible to utilize the polarization electric field generated by the self-polarization of the barium titanate particles to suppress the growth of dendrites on the surface of the negative electrode plate, while also being able to improve the problem of decreased mechanical strength of the solid electrolyte caused by the agglomeration of the barium titanate particles.
[0011] In combination with the first aspect, in certain implementations of the first aspect, the median particle size D50 of the barium titanate particles is in the range of 50 nm to 200 nm.
[0012] It should be understood that D50 may refer to the particle size corresponding to the particles with a cumulative volume particle size percentage of 50% in the barium titanate particles. D50 may represent the average particle size of the barium titanate particles.
[0013] In the above technical solution, by setting the D50 of the barium titanate particles within a suitable range, the average particle size of the barium titanate particles distributed in the second polymer is moderate, which can ensure that the barium titanate particles are self-polarized under the action of the electric field at the interface between the negative electrode plate and the composite interface layer, while also improving the problem of decreased mechanical strength of the solid electrolyte caused by agglomeration of the barium titanate particles.
[0014] In combination with the first aspect, in certain implementations of the first aspect, a thickness ratio of the interface composite layer to the polymer matrix layer ranges from 1:9 to 1:4.
[0015] In the above technical solution, by controlling the thickness ratio of the interface composite layer and the polymer matrix layer within a suitable range, the amount of material in the interface composite layer can be controlled within a suitable range, which is beneficial to reduce the cost of the secondary battery while improving the dendrite growth problem.
[0016] In combination with the first aspect, in some implementations of the first aspect, the thickness of the solid electrolyte ranges from 100 μm to 200 μm.
[0017] In the above technical solution, by setting the thickness of the solid electrolyte within a suitable range, the solid electrolyte can have good mechanical strength while reducing the impact of the solid electrolyte on the volume energy density of the secondary battery.
[0018] In combination with the first aspect, in certain implementations of the first aspect, the first polymer and the second polymer each independently include at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile and polyethylene oxide.
[0019] In the above technical solution, when the first polymer and the second polymer are made of the above materials, the polymer matrix layer and the interface composite layer can have good flexibility. In this way, when the solid electrolyte contacts the positive electrode sheet and the negative electrode sheet, good contact between the polymer matrix layer and the positive electrode sheet, and between the interface composite layer and the negative electrode sheet can be ensured, thereby reducing the contact impedance between the solid electrolyte and the positive electrode sheet, and the negative electrode sheet, which is conducive to further improving the charge and discharge performance of the secondary battery.
[0020] In some embodiments, the first polymer and the second polymer include the same material type. In this way, the close combination of the polymer matrix layer and the interface composite layer can be ensured, which is beneficial to further improve the mechanical strength of the solid electrolyte, thereby improving the safety of the secondary battery.
[0021] In combination with the first aspect, in certain implementations of the first aspect, the polymer matrix layer and the composite interface layer also include ionic compounds, and the ionic compounds include at least one of MPF6, MClO4, MTFSI and M[(CF3SO2)2N], wherein M is Li or Na.
[0022] In the above technical solution, the ionic compound in the solid electrolyte can not only provide metal ions that move between the positive electrode sheet and the negative electrode sheet, but also can be used to transmit metal ions between the positive electrode sheet and the negative electrode sheet. In addition, the specific type of the ionic compound can be determined according to the system of the secondary battery used in the specific application. For example, in a sodium ion battery, the ionic compound can be a sodium salt.
[0023] In combination with the first aspect, in certain implementations of the first aspect, the negative electrode plate includes at least one of a metallic lithium negative electrode, a metallic sodium negative electrode, a lithium alloy negative electrode, and a sodium alloy negative electrode.
[0024] In some embodiments, the lithium alloy may include at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium tin alloy, and a lithium indium alloy. The sodium alloy may include at least one of a sodium silicon alloy, a sodium lithium alloy, a sodium potassium alloy, a sodium tin alloy, and a sodium indium alloy.
[0025] In the above technical solution, the negative electrode plate can be a metal plate. Metal plates usually have a relatively serious problem of dendrite growth in secondary batteries. In the secondary battery provided in the embodiment of the present application, a solid electrolyte with a double-layer structure is provided between the metal negative electrode plate and the positive electrode plate to inhibit the growth of dendrites on the surface of the metal negative electrode plate, thereby improving the charge and discharge performance and safety of the metal negative electrode secondary battery, which is conducive to the development of high energy density metal negative electrode secondary batteries.
[0026] In combination with the first aspect, in certain implementations of the first aspect, the negative electrode plate includes at least one of a graphite negative electrode, a hard carbon negative electrode, a soft carbon negative electrode, and a graphene negative electrode.
[0027] In a second aspect, a battery pack is provided, the battery pack comprising at least one secondary battery as described in any one of the first aspect above; and a shell, wherein the at least one secondary battery is accommodated in the shell.
[0028] In a third aspect, an energy storage system is provided, which includes a power converter and a battery pack as described in the second aspect above; the power converter is used to convert the current input to the battery pack; or, the power converter is used to convert the current output from the battery pack.
[0029] The technical effects that can be achieved by the second to third aspects mentioned above can be referred to the description of the technical effects in the first aspect mentioned above, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic structural diagram of a secondary battery provided in an embodiment of the present application.
[0031] Figure 2 It is a schematic structural diagram of a secondary battery provided in an embodiment of the present application.
[0032] Figure 3 It is a schematic flow chart of a method for preparing a solid electrolyte provided in an embodiment of the present application.
[0033] Figure 4 It is a schematic diagram of the structure of a battery pack provided in an embodiment of the present application.
[0034] Figure 5 It is a structural schematic diagram of an energy storage system provided in an embodiment of the present application.
[0035] Figure 6It is a structural schematic diagram of an electric vehicle provided in an embodiment of the present application.
[0036] Figure 7 This is a scanning electron microscope (SEM) picture of the solid electrolyte of Example 1 provided in the examples of the present application.
[0037] Figure 8 It is a cross-sectional SEM image and a corresponding element distribution diagram of the solid electrolyte of Example 1 provided in the examples of the present application.
[0038] Fig. 9 It is a cycle performance diagram of the secondary batteries of Comparative Example 1 and Example 2 provided in the examples of the present application.
[0039] Fig.10 These are SEM images of the surface of the negative electrode sheet in contact with the solid electrolyte of the secondary battery of Comparative Example 1 provided in the embodiments of the present application before and after 150 cycles.
[0040] Fig.11 These are SEM images of the surface of the negative electrode sheet in contact with the solid electrolyte of the secondary battery of Example 2 provided in the examples of the present application before and after 150 cycles. DETAILED DESCRIPTION
[0041] In order to facilitate understanding of the embodiments of the present application, the following points are explained before introducing the embodiments of the present application.
[0042] In the description of the embodiments of the present application, a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way includes the endpoint values and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 50 to 200 and 80 to 160 is listed for a specific parameter, it is also expected to be understood that the range of 50 to 160 and 80 to 200 is also expected. In addition, in the description of the embodiments of the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "50 to 200" means that all real numbers between "50 to 200" have been fully listed in the embodiments of the present application, and "50 to 200" is only an abbreviation of these numerical combinations.
[0043] In the description of the embodiments of the present application, "and / or" is merely a way of describing the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone.
[0044] In the description of the embodiments of the present application, the terms "first" and "second" are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may include one or more features either explicitly or implicitly. In addition, in the description of the embodiments of the present application, "multiple" refers to two or more than two, and "at least one" and "one or more" refer to one, two or more than two.
[0045] First, the technical terms involved in the embodiments of the present application are introduced.
[0046] A secondary battery (rechargeable battery), also known as a rechargeable battery or storage battery, may refer to a battery that can be recharged to activate the active material after the battery is discharged and continue to be used.
[0047] Dendrites: During the charging process of a secondary battery, metal ions (such as lithium ions, sodium ions, etc.) are released from the positive electrode, deposited on the negative electrode surface through the conduction of the electrolyte, and further embedded in the negative electrode active material. When the metal ions are deposited unevenly on the negative electrode surface, the metal ions will form branch-like metal crystals on the negative electrode surface, which can be called dendrites.
[0048] The technical solutions in the embodiments of the present application will be described below in conjunction with the accompanying drawings.
[0049] The secondary battery provided in the embodiment of the present application can be used to store and release electric energy in scenarios such as household energy storage, industrial energy storage, communication base stations, data centers, smart photovoltaics, electric vehicles, etc. Alternatively, the secondary battery provided in the embodiment of the present application can also be used in terminal devices such as smart phones and laptops.
[0050] As described in the above background technology section, during the cycle of the secondary battery, dendrites are easily grown on the surface of the metal negative electrode, resulting in a decrease in the cycle performance and safety of the secondary battery. The current secondary batteries mainly use two types of electrolytes: liquid electrolytes and solid electrolytes. Among them, compared with liquid electrolytes, the structure of solid electrolytes is denser and thinner, which is conducive to the thinness of secondary batteries. In addition, solid electrolytes have a wider electrochemical window, which can match higher voltage positive electrode active materials, which is conducive to improving the energy density of secondary batteries. In addition, solid electrolytes have a certain mechanical strength, which can physically block the growth of dendrites on the surface of the negative electrode. Therefore, compared with liquid electrolytes, secondary batteries using solid electrolytes can have higher energy density and safety.
[0051] Figure 11 is a schematic diagram of a secondary battery 10 using a solid electrolyte provided in an embodiment of the present application. The secondary battery 10 may be, for example, a lithium ion battery, a sodium ion battery, a potassium ion battery, a magnesium ion battery or an aluminum ion battery.
[0052] like Figure 1 As shown, the core components of the secondary battery 10 may include a positive electrode sheet 11, a negative electrode sheet 12, and a solid electrolyte 13 disposed between the positive electrode sheet 11 and the negative electrode sheet 12. During the charge and discharge process of the secondary battery 10, metal ions (such as lithium ions, sodium ions, potassium ions, magnesium ions, or aluminum ions) can be embedded and extracted back and forth between the positive electrode sheet 11 and the negative electrode sheet 12 to achieve storage and release of electrical energy. For example, Figure 1 As shown, Na + Moving to the left (towards the positive electrode 11) is the process of releasing electric energy, Na + Moving to the right (towards the negative electrode sheet 12) is an energy storage process. The solid electrolyte 13 can be a carrier for the transmission of metal ions between the positive electrode sheet 11 and the negative electrode sheet 12. In addition, the solid electrolyte 13 itself is non-conductive and can separate the positive electrode sheet 11 and the negative electrode sheet 12, allowing metal ions to pass through while preventing the short circuit of the positive electrode sheet 11 and the negative electrode sheet 12, so that the electrochemical reaction of the secondary battery 10 proceeds normally.
[0053] The positive electrode sheet 11 may include a positive electrode current collector and a positive electrode active material. The positive electrode active material may be coated on the surface of the positive electrode current collector. The positive electrode current collector not coated with the positive electrode active material protrudes from the positive electrode current collector coated with the positive electrode active material. The positive electrode current collector not coated with the positive electrode active material serves as a positive electrode tab. Taking a sodium ion battery as an example, the material of the positive electrode current collector may be aluminum foil, and the positive electrode active material may include but is not limited to sodium manganese oxide, sodium cobalt oxide, and sodium iron phosphate.
[0054] The negative electrode sheet 12 may include a negative electrode current collector and a negative electrode active material. The negative electrode active material may be coated on the surface of the negative electrode current collector. The negative electrode current collector not coated with the negative electrode active material protrudes from the negative electrode current collector coated with the negative electrode active material. The negative electrode current collector not coated with the negative electrode active material serves as a negative electrode tab. Taking a sodium ion battery as an example, the material of the negative electrode current collector may be copper foil, and the negative electrode active material may include but is not limited to carbon, phosphate, titanate, metallic sodium or sodium alloy.
[0055] The solid electrolyte 13 may generally include three categories: polymer electrolyte, inorganic electrolyte and organic-inorganic composite electrolyte. The specific composition of the solid electrolyte 13 may be determined according to the system of the secondary battery 10.
[0056] Taking the secondary battery 10 as a sodium ion battery as an example, during the charging process of the secondary battery 10, sodium ions are released from the positive active material of the positive electrode plate 11, and are transferred through the solid electrolyte 13 and deposited on the surface of the negative active material of the negative electrode plate 12. However, the uneven surface structure of the negative active material may cause uneven electric field distribution at the interface between the surface of the negative active material and the solid electrolyte 13, resulting in different amounts of sodium ions deposited in different areas of the surface of the negative active material. For example, in some areas where the electric field distribution at the interface is relatively concentrated, the sodium ion deposition speed is faster and more, so it is easy to form sodium dendrites in these areas.
[0057] Although the solid electrolyte 13 can physically block the growth of sodium dendrites to a certain extent, the effect of inhibiting the growth of sodium dendrites by physical blocking is limited. When the sodium dendrites grow to a certain extent, they may still pierce the solid electrolyte 13, causing the secondary battery 10 to short-circuit. In addition, the growth of sodium dendrites will cause a part of the sodium ions to be unable to participate in the electrochemical reaction during the charge and discharge cycle, resulting in a decrease in the energy density and coulomb efficiency of the secondary battery 10. Therefore, the effect of inhibiting the growth of sodium dendrites by relying solely on the mechanical strength of the solid electrolyte 13 itself is still unable to better meet the current demand for improving the comprehensive performance of the secondary battery 10.
[0058] Based on the above content, the embodiments of the present application provide a secondary battery, a battery pack, an energy storage system and an electric vehicle, the purpose of which is to inhibit the growth of dendrites on the surface of the negative electrode plate in the secondary battery, which is beneficial to improving the charging and discharging performance and safety of the secondary battery.
[0059] Figure 2 2 is a schematic diagram of the structure of a secondary battery 200 provided in an embodiment of the present application. The secondary battery 200 may be, for example, a lithium ion battery, a sodium ion battery, a potassium ion battery, a magnesium ion battery or an aluminum ion battery.
[0060] like Figure 2 As shown, the secondary battery 200 may include a positive electrode sheet 210 , a negative electrode sheet 220 , and a solid electrolyte 230 . The solid electrolyte 230 may be disposed between the positive electrode sheet 210 and the negative electrode sheet 220 .
[0061] The solid electrolyte 230 may include a polymer matrix layer 231 and a composite interface layer 232 stacked in sequence, and the interface composite layer 232 is located between the negative electrode plate 220 and the polymer matrix layer 231. The polymer matrix layer 231 may include a first polymer (such as Figure 2 The composite interface layer 232 may include a second polymer (such as Figure 2 The composite interface layer 232 is shown in the filling pattern) and barium titanate (BaTiO3) particles 2321.
[0062] It is understood that the first polymer and the second polymer 221 can be polymers that can conduct ions but not conduct electricity, so as to serve as a carrier for the transmission of metal ions between the positive electrode plate 210 and the negative electrode plate 220. The BaTiO3 particles 2321 can be used to uniformly distribute the electric field at the interface between the negative electrode plate 220 and the solid electrolyte 230.
[0063] Specifically, if Figure 2 As shown, the composite interface layer 232 can be located between the polymer matrix layer 231 and the negative electrode plate 220, the surface of the composite interface layer 232 facing away from the polymer matrix layer 231 is in contact with the negative electrode plate 220, and the surface of the polymer matrix layer 231 facing away from the composite interface layer 232 is in contact with the positive electrode plate 210. That is to say, the composite interface layer 232 serves as an interface layer in contact between the solid electrolyte 200 and the negative electrode plate 220. Under the action of the electric field at the interface between the negative electrode plate 220 and the composite interface layer 232, the BaTiO3 particles 2321 in the composite interface layer 232 can be self-polarized to generate a polarization electric field. The direction of the polarization electric field is opposite to the direction of the electric field at the above interface, so that the electric field at the above interface can be balanced.
[0064] Furthermore, the ability of the polarization electric field to balance the electric field at the interface is related to the uniformity of the electric field distribution at the interface. Specifically, the more concentrated the electric field distribution at the interface, the stronger the ability of the polarization electric field to balance the electric field in the area; the more uniform the electric field distribution at the interface, the weaker the ability of the polarization electric field to balance the electric field in the area.
[0065] Therefore, during the charging process of the secondary battery 200, metal ions are released from the positive electrode plate 210, transmitted through the polymer matrix layer 231, and moved to the composite interface layer 232. When the electric field distribution at the interface between the negative electrode plate 220 and the composite interface layer 232 is uneven, the polarization electric field generated by the self-polarization of the BaTiO3 particles 2232 can balance the electric field in the area where the electric field distribution at the interface is relatively concentrated, so that the electric field distribution at the interface between the negative electrode plate 220 and the composite interface layer 232 is uniform.
[0066] In the above technical solution, the solid electrolyte 230 is set to a double-layer structure, and the composite interface layer 232 containing BaTiO3 particles 2321 in the double-layer structure is used as the interface layer where the solid electrolyte 230 contacts the negative electrode sheet 220. The polarization electric field generated by the BaTiO3 particles 2321 makes the electric field distribution at the interface between the negative electrode sheet 220 and the composite interface layer 232 uniform, so that the metal ions in the composite interface layer 232 can be guided to deposit uniformly on the surface of the negative electrode sheet 220. In this way, it is beneficial to suppress the growth of dendrites on the surface of the negative electrode sheet 220, and can improve the charge and discharge performance and safety of the secondary battery 200. In addition, the solid electrolyte 230 with a double-layer structure has strong mechanical strength, which can reduce the possibility of dendrites on the surface of the negative electrode sheet 220 piercing the solid electrolyte 230, which is beneficial to further improve the safety of the secondary battery 200.
[0067] In some embodiments, the negative electrode plate 220 may be a metal negative electrode, wherein the metal negative electrode plate may include at least one of a metal sodium negative electrode, a metal lithium negative electrode, a sodium alloy negative electrode, and a lithium alloy negative electrode.
[0068] In one example, the lithium alloy may include at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium tin alloy, and a lithium indium alloy. The sodium alloy may include at least one of a sodium silicon alloy, a sodium lithium alloy, a sodium potassium alloy, a sodium tin alloy, and a sodium indium alloy.
[0069] It can be understood that in the secondary battery 200 provided in the embodiment of the present application, a solid electrolyte 230 with a double-layer structure is provided between the metal negative electrode and the positive electrode plate 210 to inhibit the growth of dendrites on the surface of the metal negative electrode, thereby improving the charge and discharge performance and safety of the metal negative electrode secondary battery, which is conducive to the development of high energy density metal negative electrode secondary batteries.
[0070] In other embodiments, the negative electrode plate 220 includes at least one of a carbon-based negative electrode, a silicon-based negative electrode, and a tin-based negative electrode. Among them, the carbon-based negative electrode may include at least one of a graphite negative electrode, a hard carbon negative electrode, a soft carbon negative electrode, and a graphene negative electrode. The silicon-based negative electrode may include at least one of a silicon negative electrode, a silicon-carbon negative electrode, a silicon-oxygen negative electrode, and a silicon-metal compound negative electrode. The tin-based negative electrode may include at least one of a tin negative electrode, a tin-carbon negative electrode, a tin-oxygen negative electrode, and a tin-metal compound negative electrode.
[0071] For details about the positive electrode sheet 210 and the negative electrode sheet 220, please refer to Figure 1 The embodiments shown will not be described in detail here.
[0072] The polymer matrix layer 231 and the composite interface layer 232 of the solid electrolyte 230 are further described in detail below.
[0073] In some embodiments, the first polymer of the polymer base layer 231 may include at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, and polyethylene oxide.
[0074] It can be understood that the specific material types included in the above-mentioned first polymer are only illustrative and can be adjusted according to actual production and design requirements. For example, the first polymer can also include at least one of a derivative of polyacrylonitrile, a derivative of polyethylene oxide, polypropylene oxide, a derivative of polypropylene oxide, polymethyl methacrylate, and a derivative of polymethyl methacrylate.
[0075] It is understandable that when the first polymer is made of the above-mentioned material, the polymer matrix layer 231 can have good flexibility. In this way, when in contact with the positive electrode sheet 210, good contact between the polymer matrix layer 231 and the positive electrode sheet 210 can be ensured, thereby reducing the contact impedance between the solid electrolyte 200 and the positive electrode sheet 210, which is beneficial to improving the charge and discharge performance of the secondary battery 200.
[0076] In one example, the first polymer may be any of the above materials. For example, the first polymer may be polyvinylidene fluoride; or the first polymer may be polyvinylidene fluoride-hexafluoropropylene copolymer. In this way, the first polymer in the polymer matrix layer 231 is evenly distributed, and agglomeration caused by different types of polymer materials is avoided, thereby ensuring the mechanical strength of the solid electrolyte 230.
[0077] In some embodiments, the polymer matrix layer 231 may further include an ionic compound, which can not only provide metal ions that move between the positive electrode plate 210 and the negative electrode plate 220 , but can also be used to transport metal ions between the positive electrode plate 210 and the negative electrode plate 220 .
[0078] In one example, the ionic compound may include at least one of MPF6, MClO4, MTFSI, and M[(CF3SO2)2N], wherein M is Li or Na.
[0079] The specific type of the ionic compound can be determined according to the system of the secondary battery 200. For example, when the secondary battery 200 is a sodium ion battery, the ionic compound can be a sodium salt, and can specifically include at least one of NaPF6, NaClO4, NaTFSI and Na[(CF3SO2)2N]. That is, the solid electrolyte 230 can be a sodium ion electrolyte, and the ionic compound in the polymer matrix layer 231 can dissociate into sodium ions that can move freely.
[0080] For another example, when the secondary battery 200 is a lithium ion battery, the ionic compound may be a lithium salt, specifically at least one of LiPF6, LiClO4, LiTFSI and Li[(CF3SO2)2N]. That is, the solid electrolyte 230 may be a lithium ion electrolyte, and the ionic compound in the polymer matrix layer 231 may dissociate into lithium ions that can move freely.
[0081] It can be understood that the specific types of the above-mentioned ionic compounds are only examples, which can be adjusted according to actual production and design requirements. For example, the ionic compounds can also include at least one of MBF4, MAsF6, MPF2O2, MCF3SO3, M[(CF3SO2)2C], where M is Na or Li.
[0082] In some embodiments, similar to the first polymer, the second polymer in the composite interface layer 232 may also include at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, and polyethylene oxide.
[0083] It is understandable that when the second polymer is made of the above-mentioned material, the composite interface layer 232 can have good flexibility. In this way, when in contact with the negative electrode plate 220, good contact between the composite interface layer 232 and the negative electrode plate 220 can be ensured, thereby reducing the contact impedance between the solid electrolyte 200 and the negative electrode plate 220, which is beneficial to improving the charge and discharge performance of the secondary battery 200.
[0084] For the incomplete parts of the second polymer, please refer to the related description of the first polymer, which will not be repeated here.
[0085] In one example, the second polymer may be the same material type as the first polymer. For example, the second polymer and the first polymer may both be polyvinylidene fluoride; or, the second polymer and the first polymer may both be polyvinylidene fluoride-hexafluoropropylene. In this way, it is beneficial to ensure the close combination of the composite interface layer 232 and the polymer matrix layer 231 in the solid electrolyte 230, which is beneficial to ensure the mechanical strength of the solid electrolyte 230, thereby improving the safety of the secondary battery 200.
[0086] In some embodiments, in the composite interface layer 232, the mass ratio of the BaTiO3 particles 2321 to the second polymer may be 0.1 to 0.25. Further, the mass ratio of the BaTiO3 particles 2321 to the second polymer may be 0.15 to 0.2. For example, the mass ratio of the BaTiO3 particles 2321 to the second polymer may be 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, or the value thereof may be within the range obtained by combining any two of the above values.
[0087] It is understandable that when the mass ratio of BaTiO3 particles 2321 to the second polymer is too small, the content of BaTiO3 particles 2321 in the composite interface layer 232 is small, which is not conducive to suppressing the growth of dendrites on the surface of the negative electrode plate 220 through the polarization electric field generated by the BaTiO3 particles 2321. When the mass ratio of BaTiO3 particles 2321 to the second polymer is too large, the content of BaTiO3 particles 2321 in the composite interface layer 232 is large, and the BaTiO3 particles 2321 are easily agglomerated in the second polymer, resulting in a decrease in the mechanical strength of the solid electrolyte 230.
[0088] In the above technical scheme, by setting the mass ratio of BaTiO3 particles 2321 and the second polymer within an appropriate range, it is possible to utilize the polarization electric field generated by the self-polarization of the BaTiO3 particles 2321 to suppress the growth of dendrites on the surface of the negative electrode plate 220, while also being able to improve the problem of decreased mechanical strength of the solid electrolyte 230 caused by the agglomeration of the BaTiO3 particles 2321.
[0089] In some embodiments, the median particle size D50 of the BaTiO3 particles 2321 may be 50 nm to 200 nm. Further, the D50 of the BaTiO3 particles 2321 may be 80 nm to 150 nm. For example, the D50 of the BaTiO3 particles 2321 may be 50 nm, 60 nm, 70 nm, 80 nm, 85 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, or the value thereof may be within the range obtained by combining any two of the above values.
[0090] It is understood that D50 may refer to the particle size corresponding to the particles whose cumulative volume particle size percentage in the BaTiO3 particles 2321 reaches 50%. D50 may represent the average particle size of the BaTiO3 particles 2321. Materials with smaller particle sizes generally have larger specific surface areas. Therefore, when the D50 of the BaTiO3 particles 2321 is too small, the specific surface area of the BaTiO3 particles 2321 is large, and the BaTiO3 particles 2321 are easily agglomerated in the second polymer, resulting in a decrease in the mechanical strength of the solid electrolyte 230. When the D50 of the BaTiO3 particles 2321 is too large, the average particle size of the BaTiO3 particles 2321 is large, and the electric field effect at the interface between the negative electrode sheet 220 and the composite interface layer 232 may be difficult to induce the self-polarization of the BaTiO3 particles 2321, resulting in difficulty in using the polarization electric field generated by the BaTiO3 particles 2321 to suppress the growth of dendrites on the surface of the negative electrode sheet 220.
[0091] In the above technical solution, by setting the D50 of the BaTiO3 particles 2321 within a suitable range, the average particle size of the BaTiO3 particles 2321 distributed in the second polymer is moderate, which can ensure that the BaTiO3 particles 2321 are self-polarized under the action of the electric field at the interface between the negative electrode plate 220 and the composite interface layer 232, while also improving the problem of decreased mechanical strength of the solid electrolyte 230 caused by the agglomeration of the BaTiO3 particles 2321.
[0092] In some embodiments, the composite interface layer 232 may further include an ionic compound, and the specific type of the ionic compound may be determined according to the system of the secondary battery 200. For a specific description, please refer to the related description of the ionic compound in the polymer matrix layer 231, which will not be repeated here.
[0093] In some embodiments, continue to refer to Figure 2 , the thickness of the composite interface layer 232 is d1, and the thickness of the polymer matrix layer 231 is d2. Wherein, the range of d1 / d2 is 1:9 to 1:4. Further, the range of d1 / d2 is 1:8 to 1:6. For example, d1 / d2 can be 1 / 9, 2 / 9, 1 / 8, 5 / 36, 1 / 7, 1 / 6, 7 / 36, 1 / 5, 3 / 13, 1 / 4, or its value can be within the range obtained by combining any two of the above values.
[0094] In one example, the thickness d1 of the composite interface layer 232 may be 20 μm, and correspondingly, the thickness d2 of the polymer matrix layer 231 may be 80 μm, 87 μm, 90 μm, 100 μm, 103 μm, 120 μm, 140 μm, 144 μm, 160 μm, or 180 μm.
[0095] It is understandable that, when the thickness of the solid electrolyte 230 is constant, when the thickness d1 of the composite interface layer 232 and the thickness d2 of the polymer matrix layer 231 are small, the thickness of the composite interface layer 232 in the solid electrolyte 230 is small, resulting in a small content of BaTiO3 particles 2321, which is not conducive to suppressing the growth of dendrites on the surface of the negative electrode plate 220 through the polarization electric field generated by the BaTiO3 particles 2321. When the ratio of the thickness d1 of the composite interface layer 232 to the thickness d2 of the polymer matrix layer 231 is large, the thickness of the composite interface layer 232 in the solid electrolyte 230 is large, resulting in a large content of BaTiO3 particles 2321, which is not conducive to cost control.
[0096] In the above technical solution, by setting the ratio of the thickness d1 of the composite interface layer 232 to the thickness d2 of the polymer matrix layer 231 within a suitable range, the amount of material in the interface composite layer 232 can be controlled within a suitable range, which is beneficial to reduce the cost of the secondary battery 200 while improving the dendrite growth problem.
[0097] In some embodiments, the overall thickness d3 of the solid electrolyte 230 may be 100 μm to 200 μm. Further, the overall thickness d3 of the solid electrolyte 230 may be 120 μm to 180 μm. For example, the overall thickness d3 of the solid electrolyte 230 may be 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, or the value thereof may be within the range obtained by combining any two of the above values.
[0098] It is understandable that when the overall thickness d3 of the solid electrolyte 230 is too large, the volume energy density of the secondary battery 200 is likely to decrease. When the overall thickness d3 of the solid electrolyte 230 is too small, the mechanical strength of the solid electrolyte 230 is likely to be poor.
[0099] In the above technical solution, by setting the overall thickness d3 of the solid electrolyte 230 within a suitable range, the solid electrolyte 230 can have good mechanical strength while reducing the impact of the solid electrolyte 230 on the volume energy density of the secondary battery 200 .
[0100] The above describes the secondary battery 200 provided in the embodiment of the present application. Figure 3 The preparation method of the solid electrolyte 230 in the secondary battery 300 provided in the embodiment of the present application is exemplarily introduced.
[0101] Figure 33 is a schematic flow chart of a method 300 for preparing a solid electrolyte provided in an embodiment of the present application. It should be understood that the preparation method 300 can be used to prepare the solid electrolyte 230 .
[0102] like Figure 3 As shown, the preparation method 300 may specifically include:
[0103] S310, dissolving BATiO3 particles, a second polymer and an ionic compound in an organic solvent, and drying to form a composite interface layer.
[0104] Exemplarily, the organic solvent may be, for example, an N,N-dimethylformamide solvent.
[0105] In some embodiments, the mass ratio of BATiO 3 particles to the second polymer may range from 0.1 to 0.25.
[0106] S320, dissolving the first polymer and the ionic compound in an organic solvent to obtain a polymer matrix layer slurry.
[0107] S330, pouring the polymer matrix layer slurry obtained in S320 on the surface of the composite interface layer, and forming a polymer matrix layer after drying, thereby obtaining a solid electrolyte with a double-layer structure.
[0108] It is understandable that in each of the above steps, when drying is performed, the drying temperature and duration can be flexibly adjusted according to actual production and design requirements, and this application does not impose any restrictions on this.
[0109] For details about the preparation method 300, please refer to Figure 2 The embodiments shown will not be described in detail here.
[0110] It can be understood that the above-mentioned method 300 for preparing the solid electrolyte is only for illustration, and the embodiment of the present application does not limit the specific method for preparing the solid electrolyte, as long as the preparation method can protect the solid electrolyte described in the above embodiment.
[0111] Combine the following Figures 4 to 6 The application of the secondary battery 200 provided in the embodiment of the present application is introduced.
[0112] Figure 4 It is a schematic diagram of the structure of a battery pack 400 provided in an embodiment of the present application.
[0113] like Figure 4 As shown, the battery pack 400 may include a housing 410 and at least one Figure 2 As shown in the secondary battery 200 , at least one secondary battery 200 may be accommodated in a housing 410 .
[0114] In specific configuration, the shape of the housing 410 can be determined according to the shape of the secondary battery 200 after being assembled. For example, the shape of the housing 410 can be a hollow cube, a cuboid, or a cylinder. In some embodiments, to facilitate the placement of the secondary battery 200 in the housing 410, the housing 410 can include an upper housing 411 and a lower housing 412. The upper housing 411 can cover the lower housing 412 and form a closed space for accommodating the secondary battery 200.
[0115] In some embodiments, when the battery pack 400 includes a plurality of secondary batteries 200, the plurality of secondary batteries 200 may be connected in parallel and / or in series and then arranged in any arrangement in the housing 410. In one example, the battery pack 400 may further include a bus bar, and the plurality of secondary batteries 200 may be connected in parallel and / or in series through the bus bar.
[0116] In one example, multiple secondary batteries 200 may be integrated into at least one battery module, and then the at least one battery module may be installed in the housing 410 to form a battery pack 400. In another example, multiple secondary batteries 200 may be directly installed in the housing 410 to form a battery pack 400.
[0117] In some embodiments, the battery pack 400 may further include a battery management system, which may be used to monitor and manage parameters such as temperature and health status of the at least one secondary battery 200 , and may also be used to effectively regulate the charge and discharge functions of the at least one secondary battery 200 .
[0118] Figure 6 It is a structural schematic diagram of an energy storage system 500 provided in an embodiment of the present application.
[0119] like Figure 6 As shown, the energy storage system 500 may include a power converter 510 and a Figure 5 Battery pack 400 is shown.
[0120] The power converter 510 may be electrically connected to the battery pack 400. The power converter 510 may be used to convert the current input to the battery pack 400, or the power converter 510 may be used to convert the current output by the battery pack 400. For example, the power converter 510 may convert the AC power from the power grid into DC power, and transmit the DC power to the battery pack 400. Alternatively, the power converter 510 may convert the DC power output by the battery pack 400 into AC power, and transmit the AC power to the power grid.
[0121] Exemplarily, the energy storage system 500 may be, for example, a charging pile, a site backup power supply, a communication base station power supply, a data center backup power supply, or the energy storage system 500 may also be an energy storage system for scenarios such as household energy storage, industrial energy storage, smart photovoltaics, or electric vehicles.
[0122] Figure 6 It is a structural schematic diagram of an electric vehicle 600 provided in an embodiment of the present application.
[0123] like Figure 6 As shown, the electric vehicle 600 may include Figure 6 The energy storage system 500 shown can be used to charge an electric vehicle 600 .
[0124] Exemplarily, the electric vehicle 600 may be a pure electric vehicle, a hybrid electric vehicle, or an extended-range electric vehicle.
[0125] The following is a further description of the embodiments of the present application in a plurality of embodiments. It should be understood that the embodiments described below are exemplary and are only used to explain the embodiments of the present application, and should not be construed as limiting the embodiments of the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0126] [Example 1]
[0127] (1) Preparation of solid electrolyte:
[0128] BaTiO3 particles with a D50 of 100 nm and a second polymer polyvinylidene fluoride (PVDF) were mixed at a mass ratio of 0.1, wherein the mass of the second polymer polyvinylidene fluoride (PVDF) was 100 mg. Then sodium salt NaPF6 was added and dissolved in N,N-dimethylformamide solvent, and a uniformly mixed slurry was obtained after stirring. The slurry was then placed in an oven and dried at 60°C to obtain a composite interface layer.
[0129] The first polymer polyvinylidene fluoride (PVDF) and sodium salt NaPF6 are dissolved in N,N-dimethylformamide solvent to obtain a polymer matrix layer slurry. The mass of the first polymer polyvinylidene fluoride (PVDF) is 400 mg.
[0130] The polymer matrix layer slurry is poured on the surface of the composite interface layer, placed in an oven, and dried at 60° C. to obtain a solid electrolyte having a double-layer structure of sequentially stacked polymer matrix layers and composite interface layers.
[0131] (2) Preparation of secondary batteries:
[0132] (2.1) Preparation of positive electrode sheet:
[0133] The positive electrode active material NaNiFeMnO, the conductive agent superconducting carbon black (super P, SP) and the binder polyvinylidene fluoride (PVDF) are dissolved in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and stirred to obtain a positive electrode slurry. The positive electrode slurry is then coated on the positive electrode current collector aluminum foil by a coating device, and then dried, cold pressed and cut to obtain a positive electrode sheet.
[0134] (2.2) Preparation of negative electrode sheet:
[0135] The metallic sodium sheet is directly used as the negative electrode.
[0136] (2.3) Assembly of secondary batteries:
[0137] The prepared positive electrode sheet, negative electrode sheet and solid electrolyte are assembled into a button battery.
[0138] Specifically, in the glove box, the button battery is assembled in the order of the negative electrode shell, the spring sheet, the gasket, the negative electrode sheet, the solid electrolyte, the positive electrode sheet, the gasket and the positive electrode shell. The surface of the polymer matrix layer in the solid electrolyte contacts the positive electrode sheet, and the surface of the composite interface layer in the solid electrolyte contacts the negative electrode sheet. Then, a button battery packaging machine is used to press the assembled button batteries, and a button-type secondary battery is obtained after formation, static and other processes.
[0139] [Example 2]
[0140] Compared with the secondary battery of Example 1, Example 2 only changes the mass ratio of BaTiO3 particles and the second polymer polyvinylidene fluoride (PVDF). Specific parameters are shown in Table 1.
[0141] [Example 3]
[0142] Compared with the secondary battery of Example 1, Example 3 only changes the mass ratio of BaTiO3 particles and the second polymer polyvinylidene fluoride (PVDF). Specific parameters are shown in Table 1.
[0143] [Example 4]
[0144] Compared with the secondary battery of Example 1, Example 4 changes the D50 of BaTiO3 particles and the mass ratio of BaTiO3 particles to the second polymer polyvinylidene fluoride (PVDF). Specific parameters are shown in Table 1.
[0145] [Example 5]
[0146] Compared with the secondary battery of Example 1, Example 5 changes the D50 of BaTiO3 particles and the mass ratio of BaTiO3 particles to the second polymer polyvinylidene fluoride (PVDF). Specific parameters are shown in Table 1.
[0147] [Example 6]
[0148] Compared with the secondary battery of Example 1, Example 6 changes the D50 of BaTiO3 particles and the mass ratio of BaTiO3 particles to the second polymer polyvinylidene fluoride (PVDF). Specific parameters are shown in Table 1.
[0149] [Example 7]
[0150] Compared with the secondary battery of Example 1, Example 7 changes the D50 of BaTiO3 particles and the mass ratio of BaTiO3 particles to the second polymer polyvinylidene fluoride (PVDF). Specific parameters are shown in Table 1.
[0151] [Example 8]
[0152] Compared with the secondary battery of Example 1, Example 8 only changes the mass ratio of BaTiO3 particles and the second polymer polyvinylidene fluoride (PVDF). Specific parameters are shown in Table 1.
[0153] [Example 9]
[0154] Compared with the secondary battery of Example 1, Example 9 only changes the mass ratio of BaTiO3 particles and the second polymer polyvinylidene fluoride (PVDF). Specific parameters are shown in Table 1.
[0155] [Example 10]
[0156] Compared with the secondary battery of Example 1, Example 10 uses polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) copolymer as the first polymer and the second polymer, and changes the mass ratio of BaTiO3 particles and the second polymer polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) copolymer. Specific parameters are shown in Table 1.
[0157] [Example 11]
[0158] Compared with the secondary battery of Example 1, Example 11 uses polyacrylonitrile (PAN) as the first polymer and the second polymer, and changes the mass ratio of BaTiO3 particles and the second polymer polyacrylonitrile (PAN). Specific parameters are shown in Table 1.
[0159] [Example 12]
[0160] (1) Preparation of solid electrolyte:
[0161] BaTiO3 particles with a D50 of 100nm and the second polymer polyvinylidene fluoride (PVDF) are mixed at a mass ratio of 20:100, and then lithium salt LiPF6 is added and dissolved in N,N-dimethylformamide solvent, and stirred to obtain a uniformly mixed slurry. The slurry is then placed in an oven and dried at 60°C to obtain a composite interface layer. The mass of the second polymer polyvinylidene fluoride (PVDF) is 100mg.
[0162] The first polymer polyvinylidene fluoride (PVDF) and lithium salt LiPF6 are dissolved in N,N-dimethylformamide solvent to obtain a polymer matrix layer slurry. The mass of the first polymer polyvinylidene fluoride (PVDF) is 400 mg.
[0163] The polymer matrix layer slurry is poured on the surface of the composite interface layer, placed in an oven, and dried at 60° C. to obtain a solid electrolyte having a double-layer structure of sequentially stacked polymer matrix layers and composite interface layers.
[0164] (2) Preparation of secondary batteries:
[0165] (2.1) Preparation of positive electrode sheet:
[0166] The positive electrode active material LiNiCoMnO (NCM811), the conductive agent superconducting carbon black (super P, SP) and the binder polyvinylidene fluoride (PVDF) are dissolved in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and stirred to obtain a positive electrode slurry. The positive electrode slurry is then coated on the positive electrode current collector aluminum foil by a coating device, and then dried, cold pressed and cut to obtain a positive electrode sheet.
[0167] (2.2) Preparation of negative electrode sheet:
[0168] The metal lithium sheet is directly used as the negative electrode.
[0169] (2.3) Assembly of secondary batteries:
[0170] The secondary battery of Example 12 is assembled in the same manner as that of Example 1, which will not be described in detail herein.
[0171] [Comparative Example 1]
[0172] (1) Preparation of solid electrolyte:
[0173] 500 mg of polymer polyvinylidene fluoride (PVDF) and sodium salt were dissolved in N,N-dimethylformamide solvent and stirred to obtain a uniformly mixed slurry. The slurry was then placed in an oven and dried at 60° C. to obtain a solid electrolyte layer.
[0174] (2) Preparation of secondary batteries:
[0175] The secondary battery of Comparative Example 1 was prepared by the same method as that of Example 1, which will not be described in detail here.
[0176] The product parameters of different embodiments and comparative examples are shown in Table 1.
[0177] Table 1 Product parameters of different embodiments and comparative examples
[0178]
[0179] Next, the test process of relevant parameters is described:
[0180] 1. Structural characterization test of solid electrolyte:
[0181] SEM can be used to characterize the surface morphology and cross-sectional element distribution of the solid electrolyte prepared in the example.
[0182] Secondary battery cycle performance test at 2.25°C:
[0183] Sodium ion battery: At 25°C, using the LAND CT2001A test system, the sodium ion battery was charged to 4.0V at a constant current of 0.5C, then charged to a current of less than 0.05C at a constant voltage of 4.0V, and then discharged to 2.0V at a constant current of 0.5C. This is a charge and discharge process. The charge and discharge were repeated in this way, and the capacity retention rate of the sodium ion battery after 150 cycles was calculated.
[0184] The capacity retention rate (%) of the sodium ion battery after 150 cycles = (discharge capacity at the 150th cycle / discharge capacity at the first cycle) × 100%.
[0185] Lithium-ion battery: At 25°C, using the LAND CT2001A test system, the lithium-ion battery is charged to 4.3V at a constant current of 0.5C, then charged to a current of less than 0.05C at a constant voltage of 4.3V, and then discharged to 2.8V at a constant current of 0.5C. This is a charge and discharge process. Repeat the charge and discharge in this way, and calculate the capacity retention rate of the lithium-ion battery after 150 cycles.
[0186] The capacity retention rate (%) of the lithium-ion battery after 150 cycles = (discharge capacity at the 150th cycle / discharge capacity at the first cycle) × 100%.
[0187] 3.Dendrite condition test:
[0188] The sodium ion battery before and after 150 cycles at 25° C. was disassembled, the negative electrode sheet was taken out, and then the morphology of the surface where the negative electrode sheet contacts the solid electrolyte was photographed by SEM.
[0189] According to the structural test characterization method of the solid electrolyte, the solid electrolyte obtained in Example 1 was characterized using SEM. The characterization results are as follows: Figure 7 and Figure 8 .in, Figure 7 (a) is a surface SEM image of the polymer matrix layer in the solid electrolyte obtained in Example 1, Figure 7 (b) is a surface SEM image of the composite interface layer in the solid electrolyte obtained in Example 1. Figure 8 (a) is a cross-sectional SEM image of the solid electrolyte obtained in Example 1. Figure 8 (b), (c) and (d) are Figure 8 Distribution diagram of F element, Ti element and Ba element on the cross section of the solid electrolyte shown in (a).
[0190] The secondary batteries obtained in Comparative Example 1 and Examples 1-12 were tested for cycle performance according to the secondary battery cycle performance test method at 25°C. The results are shown in Table 2. Fig. 9 The battery cycle performance diagram of Example 2 and Comparative Example 1 measured after 150 cycles at 25° C. is shown.
[0191] According to the above-mentioned dendrite test method, SEM images of the surface of the negative electrode plate in contact with the solid electrolyte in Example 2 and Comparative Example 1 were taken before and after 150 cycles. The results are as follows: Fig.10 and Fig.11 As shown. Among them, Fig.10 (a) shows a surface SEM image of the surface of the negative electrode sheet in contact with the solid electrolyte in Comparative Example 1 before cycling. Fig.10 (b) shows a surface SEM image of the surface of the negative electrode sheet in contact with the solid electrolyte in Comparative Example 1 after 150 cycles. Fig.11 (a) shows a surface SEM image of the surface of the negative electrode sheet in contact with the solid electrolyte in Example 2 before cycling. Fig.11 (b) shows a surface SEM image of the surface of the negative electrode plate in contact with the solid electrolyte in Example 2 after 150 cycles.
[0192] Table 2 Battery cycle performance data of comparative examples and different embodiments
[0193]
[0194] Combination Figure 7 (a) and Figure 7 As can be seen from (b) in the figure, the surface of the solid electrolyte prepared in Example 1 is relatively uniform and dense as a whole, without obvious agglomerates, so that the solid electrolyte can have good contact with the negative electrode sheet and the positive electrode sheet, and the contact impedance between the solid electrolyte and the positive electrode sheet and the negative electrode sheet is small.
[0195] like Figure 8 As shown in (a) to (d) in the solid electrolyte prepared in Example 1, the F element is distributed throughout the entire cross section, because both the polymer matrix layer and the composite interface layer contain polymer polyvinylidene fluoride (PVDF), while the Ba element and the Ti element are distributed below the entire cross section, because only the composite interface layer contains BaTiO3 particles. Therefore, Example 1 prepared a solid electrolyte with a double-layer structure, in which the polymer matrix layer is located below the composite interface layer. Figure 8 The upper layer of the solid electrolyte described in (a), the interface composite layer is located at Figure 8 The lower layer of the solid electrolyte shown in (a).
[0196] It can be seen from Table 2 that compared with Comparative Example 1, the capacity retention rates of the sodium ion batteries and lithium ion batteries in Examples 1, 10, 11 and 12 after 150 cycles are significantly improved, indicating that in the secondary battery provided in the embodiments of the present application, a solid electrolyte with a double-layer structure of a polymer matrix layer and a composite interface layer, and a composite interface layer containing BaTiO3 particles as the interface layer for contact between the solid electrolyte and the negative electrode plate, can improve the electrical performance of the secondary battery.
[0197] Depend on Fig. 9 It is even more obvious that in the secondary battery provided in the embodiment of the present application, the sodium ion battery using the double-layer solid electrolyte containing BaTiO3 particles can maintain a capacity of up to 97.7% after 150 cycles at 25°C, while the sodium ion battery without the double-layer solid electrolyte has a capacity maintenance rate of 95% after 150 cycles at 25°C. This once again proves that in the secondary battery provided in the embodiment of the present application, the use of the double-layer solid electrolyte containing BaTiO3 particles has a beneficial effect on the charge and discharge performance of the secondary battery.
[0198] Further integration Fig.10As can be seen from (a) and (b) in Figure 1, when the sodium-ion battery does not use a double-layer solid electrolyte containing BaTiO3 particles, there is obvious sodium dendrite growth on the surface of the negative electrode after 150 cycles compared to before the cycle. Fig.11 It can be seen from (a) and (b) that when the sodium ion battery uses a double-layer solid electrolyte containing BaTiO3 particles, the surface morphology of the negative electrode plate after 150 cycles does not change significantly compared to before the cycle, and there is no obvious sodium dendrite growth. This proves that in the secondary battery provided in the embodiment of the present application, the composite interface layer containing BaTiO3 particles is used as the interface layer where the solid electrolyte contacts the negative electrode plate, which can inhibit the growth of sodium dendrites on the surface of the negative electrode plate, thereby improving the safety and charge and discharge performance of the secondary battery.
[0199] Furthermore, by comparing the data of Examples 1-3 and Examples 8-9 in Table 1, it can be seen that by controlling the mass ratio of the BaTiO3 particles and the second polymer in the composite interface layer of the solid electrolyte within a suitable range, the effect of the BaTiO3 particles in the composite interface layer in inhibiting the growth of dendrites on the surface of the negative electrode can be further improved, which is beneficial to further improve the safety and charge and discharge performance of the sodium ion battery.
[0200] By comparing the data of Example 2 and Examples 4-7 in Table 1, it can be seen that by controlling the D50 of the BaTiO3 particles in the composite interface layer of the solid electrolyte within a suitable range, the effect of the BaTiO3 particles in the composite interface layer in inhibiting the growth of dendrites on the surface of the negative electrode can be further improved, which is beneficial to further improve the safety and charge and discharge performance of the sodium ion battery.
[0201] In summary, in the secondary battery provided in the embodiments of the present application, by providing a solid electrolyte with a double-layer structure having a polymer matrix layer and a composite interface layer, and using a composite interface layer containing BaTiO3 particles as the interface layer for contact between the solid electrolyte and the negative electrode plate, the growth of dendrites on the surface of the negative electrode plate can be suppressed, thereby improving the secondary charge and discharge performance and safety.
[0202] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A secondary battery, characterized in that: include: A positive electrode sheet, a negative electrode sheet and a solid electrolyte, wherein the solid electrolyte is located between the positive electrode sheet and the negative electrode sheet; Wherein, the solid electrolyte comprises: a polymer matrix layer, the polymer matrix layer comprising a first polymer; a composite interface layer, the composite interface layer comprising a second polymer and barium titanate particles; The polymer matrix layer and the composite interface layer are stacked in sequence, and the composite interface layer is located between the polymer matrix layer and the negative electrode plate.
2. The secondary battery according to claim 1, characterized in that: In the composite interface layer, the mass ratio of the barium titanate particles to the second polymer ranges from 0.1 to 0.
25.
3. The secondary battery according to claim 1 or 2, characterized in that: The median particle size D50 of the barium titanate particles ranges from 50 nm to 200 nm.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: The thickness ratio of the composite interface layer to the polymer matrix layer ranges from 1:9 to 1:
4.
5. The secondary battery according to any one of claims 1 to 4, characterized in that: The thickness of the solid electrolyte ranges from 100 μm to 200 μm.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The first polymer and the second polymer include the same type of material; Wherein, the first polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile and polyethylene oxide.
7. The secondary battery according to any one of claims 1 to 6, characterized in that: The polymer matrix layer and the composite interface layer also include ionic compounds, and the ionic compounds include at least one of MPF6, MClO4, MTFSI and M[(CF3SO2)2N], wherein M is Li or Na.
8. The secondary battery according to any one of claims 1 to 7, characterized in that: The negative electrode plate includes at least one of a metal lithium negative electrode, a metal sodium negative electrode, a lithium alloy negative electrode and a sodium alloy negative electrode.
9. The secondary battery according to any one of claims 1 to 7, characterized in that: The negative electrode plate includes at least one of a graphite negative electrode, a hard carbon negative electrode, a soft carbon negative electrode and graphene.
10. A battery pack, characterized in that: include: At least one secondary battery according to any one of claims 1 to 9; A housing in which at least one secondary battery is accommodated.
11. An energy storage system, characterized in that: include: A power converter and a battery pack as claimed in claim 10; The power converter is used to convert the current input to the battery pack; Alternatively, the power converter is used to convert the current output by the battery pack.